MEKANISME LAYANAN BIMBINGAN AKADEMIK DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA DI INSTITUT AGAMA ISLAM NEGERI PALU - Andi Anirah (ISTIQRA, 2016)
This study aims to determine the mechanism of academic guidance services, the role of academic lecturers, lecturers and academic efforts in improving student learning motivation at IAIN Palu. The method used in this research is descriptive qualitative method.The results showed that the mechanism of academic guidance services at IAIN Palu was first determined Academic Advisors who meet the criteria. Second, provide good academic guidance services. Third, provide guidance and assistance in the form of consultations, either individually or in groups. The role of the lecturers Academic Advisors, as a motivator, adviser, model, counselor and facilitator of students in the lecture, at IAIN Palu is it quite good, but some lecturers academic role is not optimal, it is seen most students only met with their academic advisors when signing KRS. The efforts of academic advisors in improving student learning motivation at IAIN Palu is to provide consulting services either by providing a special time for students, make a report to the head of the faculty of the coaching process, providing motivation to study harder. Therefore, the academic coaching at IAIN Palu needs to be managed effectively and efficiently so that it can mean for the educational process of students. Students are expected to be more open to their Academic Advisors discussing academic and non academic problems. Students should try to improve the harmony of their relationship with the Academic Advisors. For the Institute to improve the quality of guidance, it may be held intensive training to the Academic Advisors, and the regular monitoring of the student learning outcomes that can be implemented immediately when found students' academic problems